2022
DOI: 10.3390/metabo12010042
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Connectivity and Hemodynamic-Metabolic Coherence of Human Prefrontal Cortex at Rest and Post Photobiomodulation Assessed by Dual-Channel Broadband NIRS

Abstract: Billions of neurons in the human brain form neural networks with oscillation rhythms. Infra-slow oscillation (ISO) presents three main physiological sources: endogenic, neurogenic, and myogenic vasomotions. Having an in vivo methodology for the absolute quantification of ISO from the human brain can facilitate the detection of brain abnormalities in cerebral hemodynamic and metabolic activities. In this study, we introduced a novel measurement-plus-analysis framework for the non-invasive quantification of pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 86 publications
9
31
0
Order By: Relevance
“…Moreover, the observation that tPBM enabled to strongly modulate myogenic oscillation within cerebral hemodynamic ISO across the human whole head is also highly consistent with our recent article (Wang et al, 2022). Accordingly, tPBM significantly enhanced the spectral amplitude of [HbO] in the myogenic bands by 23% near the tPBM site compared to the sham condition (Wang et al, 2022). Putting all the knowledge and recent findings together, our observations could be explained or interpreted as follows: tPBM started a cascade process by (1) first triggering the release of NO (besides photo-oxidation of CCO), (2) causing increases in endogenic oscillation and FC, (3) giving rise to the relaxation of the vascular smooth muscle, and thus (4) resulting in changes in myogenic oscillations as well as increases in myogenic FC.…”
Section: Effects Of Tpbm On Myogenic Oscillation Of [Hbo]supporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, the observation that tPBM enabled to strongly modulate myogenic oscillation within cerebral hemodynamic ISO across the human whole head is also highly consistent with our recent article (Wang et al, 2022). Accordingly, tPBM significantly enhanced the spectral amplitude of [HbO] in the myogenic bands by 23% near the tPBM site compared to the sham condition (Wang et al, 2022). Putting all the knowledge and recent findings together, our observations could be explained or interpreted as follows: tPBM started a cascade process by (1) first triggering the release of NO (besides photo-oxidation of CCO), (2) causing increases in endogenic oscillation and FC, (3) giving rise to the relaxation of the vascular smooth muscle, and thus (4) resulting in changes in myogenic oscillations as well as increases in myogenic FC.…”
Section: Effects Of Tpbm On Myogenic Oscillation Of [Hbo]supporting
confidence: 91%
“…Furthermore, the strong modulation ability of tPBM on endogenic oscillation within cerebral hemodynamic ISO across the human whole head seen in this study is highly consistent with and well supported by another just-published article of our group (Wang et al, 2022). The report was based on dual-channel, bbNIRS measurements taken from a completely different group of participants and performed by different operators.…”
Section: Effects Of Tpbm On Endogenic Oscillation Of [Hbo]supporting
confidence: 89%
See 2 more Smart Citations
“…In this study, we focus on the conventional NIRS with the wavelength range from 650 to 950 nm, which facilitates quantitative changes of the hemodynamic (Boas and Franceschini, 2011) and metabolic state of various tissue types, such as the breast (Cerussi et al, 2011;Jiang et al, 2013), muscle (Ferrari et al, 2011;Wang X. et al, 2016), or brain (Villringer et al, 1993;Smith, 2011;Tian et al, 2016;Wang et al, 2017;Pruitt et al, 2020;Wang et al, 2022). In this spectral range, the three main chromophores of interest in most NIRS-based studies are oxyhemoglobin (HbO), deoxyhemoglobin (HHb), and cytochrome-c-oxidase (CCO) (Heekeren et al, 1999;Kolyva et al, 2012;Bale et al, 2014;Kolyva et al, 2014;Wang X. et al, 2016;Wang et al, 2017;Wang et al, 2022). Numerous studies have revealed the potential use of NIRS in a wide range of clinical applications, including neuromonitoring (Lange and Tachtsidis, 2019;Pinti et al, 2020), metabolic state observation (Durduran et al, 2010;Hamaoka et al, 2011), or cancer detection (Nioka and Chance, 2005;Cerussi et al, 2011;Jiang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%